Warehouse Operations Data Structure (WODS): A data structure developed for warehouse operations modeling. (October 2017) - Ansari, Mohammadnaser; Smith, Jeffrey S.
Highlights: We defined a new data structure for modeling warehouse operations. Physical warehouse is represented by graph. A set of sample code is provided for the use of research community. Abstract: Generally accepted data structures and predefined paradigms such as geographic information system (GIS) in research domains enhance researchers experience and efficiency by providing defined data structures and file formats. Warehousing and related topics represent one of the most studied areas in supply chain with no predefined standards or data structures when it comes to developing warehouse operation related programs and code. In this paper, we propose WODS, a new data structure that integrates, stores, edits, analyzes, and displays data related to all aspects of warehouse modeling and development. The paper also describes a set of tools to demonstrate the use of WODS which can also play as a starting point that facilitates the process of modeling a warehouse operation program.